BUDAYA JAWA DALAM DIASPORA: TINJAUAN PADA MASYARAKAT JAWA DI SURINAME - - Darmoko (Fakultas Bahasa Seni dan Budaya, 2016)
Javanese society and culture has been forged by the situation and condition of the times centuries. Cultural influences from outside, such as the Hindu - Buddhist, Islamic, Chinese, and European, indigenous cultures should lead to